2010
DOI: 10.2466/08.09.17.pr0.107.5.463-479
|View full text |Cite
|
Sign up to set email alerts
|

Moral Reasoning and Moral Orientation of U.S. and Turkish University Students

Abstract: Participants from an individualistic society (U.S.A.) were compared with participants from a collectivistic society (Turkey) in terms of moral reasoning and orientation (justice and care). A total of 396 undergraduates (203 U.S. students, 193 Turkish students) between the ages of 18 and 46 years were administered the original version of the Defining Issues Test and the Measure of Moral Orientation. Turkish participants received higher mean principled scores than did the U.S. participants, and female participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…One important criticism came from Haidt (2001), who believed that reasoning plays a limited role in the production of moral judgment, and that conscious reasoning may come in after the initial intuitive judgment. Regardless of these criticisms, Kohlberg’s theory still generally receives considerable support (Kuyel & Glover, 2010; Thoma, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One important criticism came from Haidt (2001), who believed that reasoning plays a limited role in the production of moral judgment, and that conscious reasoning may come in after the initial intuitive judgment. Regardless of these criticisms, Kohlberg’s theory still generally receives considerable support (Kuyel & Glover, 2010; Thoma, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Let h spur and h 1 be the amplitudes of spur and input signal in decibels, as shown in (9) and (10) Note that, (9) shows that the spur amplitude is strongly dependent on the frequency of input signal. For every doubling of the input frequency, the spur amplitude increases by about 6 dB.…”
Section: Sj Estimationmentioning
confidence: 99%
“…[6] proposed an FFT-based jitter measurement method for separating random jitter from deterministic jitter. Other examples includes IEEE standard 1057 [7], Analog Device Inc. [8], and Texas Instruments Inc. [9,10]. These three methods are all dual-frequency tests where two measurements are required: a low frequency signal test and a high frequency signal test.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that Gilligan and other ethic of care researchers have stated that the difference between genders on the score is not biologically based, rather it is a result of socialization. Several studies using the MMO have found significant gender differences with females scoring higher on care than males and one study finding differences between a group of Turkish graduate students and U.S. graduate students (Kuyel and Glover 2010). Other self-administered measures of moral orientation and the care ethic have been developed and tested but provided mixed results in support for a gendered difference in moral orientation (Skoe 2014;Yacker and Weinberg 1990).…”
Section: Gender Differences On the Mmomentioning
confidence: 99%